2022
DOI: 10.3390/molecules27154817
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Proteomic Analysis of Chlorella sorokiniana, Chloroidium saccharofilum, and Chlorella vulgaris Cells Cultured in Autotrophic, Photoheterotrophic, and Mixotrophic Cultivation Modes

Abstract: Chlorella is one of the most well-known microalgal genera, currently comprising approximately a hundred species of single-celled green algae according to the AlgaeBase. Strains of the genus Chlorella have the ability to metabolize both inorganic and organic carbon sources in various trophic modes and synthesize valuable metabolites that are widely used in many industries. The aim of this work was to investigate the impact of three trophic modes on the growth parameters, productivities of individual cell compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…IF1 (encoded by S14e , S18e ), IF2 (encoded by S13e ), and IF3 are three important initiation factors in protein translation; RF1 (S6) and RF2 are two “class I” release factors involved in recognizing stop codons (Ramakrishnan 2002 ); Sec61 is related to protein translocation and targeted delivery (Sitia and Braakman 2003 ); eIF2α is related to dimer formation and protein binding during protein synthesis (Sitia and Braakman 2003 ); the stress-inducible 70-kDa heat shock protein (Hsp70) belongs to the chaperone family, which mainly binds and releases polypeptides in the ATP-dependent cycle (Fewell et al 2001 ); Hsp90 chaperones are abundant essential proteins that are associated with dimerization and preventing denatured proteins from aggregation in vitro (Fewell et al 2001 ); and COPII (Sec13/31) is related to the formation of vesicles by protein packaging (Fewell et al 2001 ). To sum up, as demonstrated by the results and literature data (Piasecka and Baier 2022 ), this study indicated that the photoheterotrophic condition mainly promotes the translocation, binding, de-glycosylation, dimer formation, protein targeted delivery, and vesicle formation of protein processing, thus to improve the protein content in the C. vulgaris .…”
Section: Discussionsupporting
confidence: 60%
“…IF1 (encoded by S14e , S18e ), IF2 (encoded by S13e ), and IF3 are three important initiation factors in protein translation; RF1 (S6) and RF2 are two “class I” release factors involved in recognizing stop codons (Ramakrishnan 2002 ); Sec61 is related to protein translocation and targeted delivery (Sitia and Braakman 2003 ); eIF2α is related to dimer formation and protein binding during protein synthesis (Sitia and Braakman 2003 ); the stress-inducible 70-kDa heat shock protein (Hsp70) belongs to the chaperone family, which mainly binds and releases polypeptides in the ATP-dependent cycle (Fewell et al 2001 ); Hsp90 chaperones are abundant essential proteins that are associated with dimerization and preventing denatured proteins from aggregation in vitro (Fewell et al 2001 ); and COPII (Sec13/31) is related to the formation of vesicles by protein packaging (Fewell et al 2001 ). To sum up, as demonstrated by the results and literature data (Piasecka and Baier 2022 ), this study indicated that the photoheterotrophic condition mainly promotes the translocation, binding, de-glycosylation, dimer formation, protein targeted delivery, and vesicle formation of protein processing, thus to improve the protein content in the C. vulgaris .…”
Section: Discussionsupporting
confidence: 60%
“…As depicted in Figure 3 a, we selected Chlorella as a representative microalga and dispersed it in an aqueous phase to create water-in-oil Pickering emulsions that encased Chlorella cells. According to the literature [ 63 , 64 ], Chlorella cells can not only grow through photoautotrophs but also through organic carbon sources under heterotrophic conditions. Even if there is no light energy input for a period of time, it can survive for a long time by consuming organic matter generated by photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Protein fractions from C. vulgaris exhibit a wide range of molecular weights, varying from 14 to 116 kDa, with their expression being influenced by growth conditions (photoheterotrophic, mixotrophic and autotrophic) [ 11 ]. Notably, proteins in photoheterotrophic and mixotrophic cultures had shown higher molecular weights (28–116 kDa) than those in autotrophic cultures (14–23 kDa), with high-density bands at 28 to 34 and 66 kDa, as reported by Piasecka et al [ 11 ], analysing mass spectrometry combined with two-dimensional gel electrophoresis. Among the proteins in photoheterotrophic C. vulgaris cultures, those associated with the cytoskeleton (49–77 kDa) or involved in stress response in the chloroplast (71–81 kDa) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Among the proteins in photoheterotrophic C. vulgaris cultures, those associated with the cytoskeleton (49–77 kDa) or involved in stress response in the chloroplast (71–81 kDa) were identified. Piasecka et al [ 11 ] and Khairy et al [ 12 ] detected two high-density protein bands at 39 and 75 kDa in C. vulgaris without characterizing them, using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Similarly, Tejano et al [ 13 ] identified, with a similar technique, ten predominant proteins in Chlorella sorokiniana , ranging from 7.8 to 109 kDa, with some being chloroplast-related proteins such as rubisco (ribulose-1,5-biphosphate carboxylase oxygenase) activase, phosphoglycerate kinase, heat shock proteins and Fe-superoxide dismutase.…”
Section: Introductionmentioning
confidence: 99%